OBETICHOLIC ACID: AN INSIGHT INTO A QUANTITATIVE DETERMINATION AND METHODOLOGICAL VALIDATION THROUGH NUCLEAR MAGNETIC RESONANCE - SAHU, RAKESH; MISHRA, RAKHI; MAJEE, CHANDANA; KUMAR, AJAY; MAZUMDER, RUPA (International Journal of Applied Pharmaceutics, 2020)
Objective: The research work unveils the use of nuclear magnetic resonance (NMR) technique for quantitative determination and method validation of obeticholic acid. As standard expository methodology for more up to date medications or formulations may not be available in pharmacopeias, hence it is fundamental need to create novel analytical procedures which should be precise and accurate. Methods: Proton (1H) and carbon (13C) NMR analysis were initially performed to confirm the preliminary authenticity of obeticholic acid API. Method validation was accomplished on the basis of standard guidelines for the parameters, in which tetramethylbenzene as an internal standard and deuterated dimethyl sulfoxide as a diluent were used to assess the obeticholic acid. Results: For the quantification of the drug, the proton nuclear magnetic resonance signals at 0.602 ppm and 6.86 ppm corresponding to the analyte proton of drug and internal standard respectively were used. The curve equation calculated from the regression method, the relative-standard-deviation and correlation-coefficient were found to be 0.743% and 0.9989 respectively, indicating good linearity. Consequently, the quantitative assay of the drug was found to be 99.91% in linearity with limit of detection and quantification values as 0.0773 mg and 0.2344 mg respectively, making successful the study of method validation for obeticholic acid. Conclusion: The advantage of the method was that no reference standard of analyte drug was required for quantification and method validation. The method is non-destructive and can be applied for quantification of drug in commercial pharmaceutical formulation products.